Terceirização e poder público: o caso das serventes merendeiras no município de São Carlos (SP) - Araújo, Lucas Henrique (Universidade Federal de São Carlos, 2024)
The aim of this study was to analyze the impact of outsourcing on the hiring of Servants in the municipality of São Carlos (SP), through the creation of the position of Food Service. Using interviews and document analysis, we investigated the working conditions of food service workers, who are civil servants, and food service assistants, who are food service assistants, and outsourced employees. The analysis was also related to transformations in the world of work in the context of flexible accumulation and neoliberalism. The conclusion is that outsourcing in the hiring of catering servers in São Carlos, through the position of Catering Service Auxiliary results in precariousness, highlighting disparities in benefits, stability, and union organization. These results reinforce the urgency to reconsider outsourcing policies, emphasizing their negative impacts on working conditions and the quality of life of workers.
Outsourcing in the public service: the case of the catering service auxiliary in the municipality of São Carlos (SP)
Keywords: Terceirização; Reforma trabalhista; Precarização do trabalho; Merendeiras no serviço público; Outsourcing; Labor reform; Precariousness of work; Catering service auxiliary; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS